Analisis Wacana Kritis Teun A. Van Dijk Pada Iklan Skincare Emina: Sunscreen Spf 35 – Bright Glow & Acne Clear 30s - Sinaga, Yesa; Aritonang, Miftahul Nurjanah; Siahaan, Laras; Nainggolan , Indanian; Oky Fardian Gafari (eScience Humanity Journal, 2025)
This reseach aims to examine the critical discourse in Emina’s skincare advertisement, specifically the Sunscreen SPF 35 – Bright Glow & Acne Clear 30s, through the application of Teun A. Van Dijk’s Critical Discourse Analysis (CDA) framework. Advertisements in the beauty industry often shape societal perceptions of beauty standards, influencing consumer behavior and emotional engagement. By applying Van Dijk’s model, this research examined three key dimensions: macrostructure (textual theme), superstructure (narrative structure), and microstructure (linguistic elements). This study uses a qualitative case study approach with data collected through observation and transcription of selected advertisements from YouTube. The findings revealed that the macrostructure emphasized skin protection against UV rays, promoting the product’s practicality and effectiveness. The superstructure presented a compelling narrative with orientation, complication, and reorientation stages to highlight product benefits. The microstructure analysis identified rhetorical devices such as code-switching, personification, and positive affirmations to enhance audience appeal. The study concluded that the advertisement not only marketed the product but also reinforced specific beauty ideals, linking clear, glowing skin to societal acceptance. This research provides insights into how advertisements influence youth perceptions and underscores the need for more inclusive beauty representations.